Análise empírica da excelência na entrega de serviços de crédito: dos conceitos abstratos a uma escala operacional pioneira - Luiz Carlos dos Santos (2004)
Outdoing their competitors in terms of service delivery is the target every company striving for leadership in their segments wishes attain. However, what does superior delivery consist of? The use of a strict methodology applied to the collection and analysis of primary data among financial executives and other key decision-makers of big and medium sized companies operating in Brazil, led to the identification of the main variables and indicators associated to the attribute delivery within the context of bank credit financial services in the domestic market. Once in possession of such indicators, an original and customized scale was designed, capable of measuring the quality of services banks deliver to that public, opening the way for managerial aspects of great relevance to be unearthed, such as, for example, how the performance among competitors compare the basis for a differentiation and positioningstrategy; the longitudinal performance of one finance agent; the evaluation and comparison of regional divisions of the same bank, which will present executives with a detailed diagnosis for future corrective and strategic actions. By means of this process, statements of great valueto executives in the financial sector have been collected and transposed to the project. Triangulation tactics, characterized by the use of a variety of methods, techniques, publics and contexts, lent qualitative rigor to the final indicators of the scale designed, and the size of sample of respondents surpassed the mean figure recommended by methodologists, thus reinforcing, in terms of substance, the confirmatory results obtained from quantitative validations done through the statistical treatment of the data. In the academic field, among other outcomes, the work pointed out a detailed description of the modus operandi for theconstruction of scales, besides a methodological schedule that will prove invaluable for future researchers. Additionally, a sets of hypotheses was generated, opening real possibilities for future field research. The efforts made to decode the attribute delivery within the realm of marketing of services were seen as a major breakthrough by renowned authors in themarketing field such as Philip Kotler, Mary Jo Bitner and Valarie Zeithaml, whose exclusive statements, collected by the author, were transposed to the present work. The academic centers dealing with strategy and theories on the marketing of services, the agents of commercial credit in Brazil and the companies, especially intensive capital companies, will further strengthen by means of this academic contribution.